If it's not what You are looking for type in the equation solver your own equation and let us solve it.
96=(4+2x)(x)
We move all terms to the left:
96-((4+2x)(x))=0
We add all the numbers together, and all the variables
-((2x+4)x)+96=0
We calculate terms in parentheses: -((2x+4)x), so:We get rid of parentheses
(2x+4)x
We multiply parentheses
2x^2+4x
Back to the equation:
-(2x^2+4x)
-2x^2-4x+96=0
a = -2; b = -4; c = +96;
Δ = b2-4ac
Δ = -42-4·(-2)·96
Δ = 784
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{784}=28$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-28}{2*-2}=\frac{-24}{-4} =+6 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+28}{2*-2}=\frac{32}{-4} =-8 $
| 8t-8+7t+1=180 | | 2x+72=100 | | 5(X-6X/3x)=0 | | y-5.4=1.12 | | y-5.6=0.74 | | 2x=3x-625 | | y-7.6=0.17 | | W-60=5w-20 | | a+35=-5 | | 3x+25=2x+28 | | y-3.9=0.56 | | y-2.1=0.59 | | 5h+7=-h+55 | | y-2.7=0.66 | | 6(x)^3-8x-3=0 | | C+12=b+b | | x+.13X=534996.25 | | y+3.2=5.43 | | 7x-6(x+3/2)=8 | | y+3.42=7.2 | | y+3.1=5.56 | | 2x+14+6x+14+64=180 | | 2y+3=3-8 | | 8m+3-3m=55.5 | | 45x=10= | | 6-(-21/a)=-3 | | 56=-48-8y56=-48-8y | | 2x+77=8x+5 | | S+4=p | | f(-4)=4(-4)-1 | | 8(u-2)=3(u+5) | | (3x+8)/(2x-7)=0 |